2021
DOI: 10.3389/fmed.2021.636547
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Managing Sepsis in Patients With Cancer in the Era of Antimicrobial Resistance

Abstract: Sepsis is a frequent complication in immunosuppressed cancer patients and hematopoietic stem cell transplant recipients that is associated with high morbidity and mortality rates. The worldwide emergence of antimicrobial resistance is of special concern in this population because any delay in starting adequate empirical antibiotic therapy can lead to poor outcomes. In this review, we aim to address: (1) the mechanisms involved in the development of sepsis and septic shock in these patients; (2) the risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 148 publications
1
37
0
2
Order By: Relevance
“…In the solid-organ transplant recipients, the independent risk factors were infected bacteria resistant to extended-spectrum cephalosporins, age, and antifungal drugs ( Anesi et al., 2021 ). In the patients with cancer, the independent risk factors were comorbidities, age, underlying diseases (mainly hematological malignancies), infection resources, types of microbial infections, hypoalbuminemia, antibiotic therapy, antibiotic-resistant organisms, shock, and ICU admission ( Gudiol et al., 2011 ; Marín et al., 2015 ; Torres et al., 2015 ; Satlin et al., 2016 ; Marín et al., 2019 ; Martinez-Nadal et al., 2020 ; Gudiol et al., 2021 ). Many studies mainly showed the prognostic risk factors of an immunosuppressive disease in different types of microbial infections or a microbial infection in different types of IS; the prognostic predictors of mortality in overall bloodstream infection in IS status were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the solid-organ transplant recipients, the independent risk factors were infected bacteria resistant to extended-spectrum cephalosporins, age, and antifungal drugs ( Anesi et al., 2021 ). In the patients with cancer, the independent risk factors were comorbidities, age, underlying diseases (mainly hematological malignancies), infection resources, types of microbial infections, hypoalbuminemia, antibiotic therapy, antibiotic-resistant organisms, shock, and ICU admission ( Gudiol et al., 2011 ; Marín et al., 2015 ; Torres et al., 2015 ; Satlin et al., 2016 ; Marín et al., 2019 ; Martinez-Nadal et al., 2020 ; Gudiol et al., 2021 ). Many studies mainly showed the prognostic risk factors of an immunosuppressive disease in different types of microbial infections or a microbial infection in different types of IS; the prognostic predictors of mortality in overall bloodstream infection in IS status were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients suffer from immunosuppression due to the alteration of the phagocytic activity of the neutrophils and monocytes through chemo- and radiotherapy ( 25 ). Cytostatic drugs and monoclonal antibodies alter lymphocytes and natural killer cells and prolong lymphopenia ( 26 , 27 ). This alteration in immunity in cancer patients made them liable to sepsis with associated high mortality ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients are particularly at risk for infection and sepsis [ 18 , 192 ]. Thus, early detection and management of sepsis, including source control of the infection (e.g., removal of tunneled central venous catheter systems) and optimized antibiotic use based on the pharmacokinetics and pharmacodynamics changes observed in AKI are essential, particularly in patients with neutropenia [ 18 , 193 ]. A review of patients’ charts to ascertain the cumulative exposure to chemo- and immunotherapeutic agents and other medications is important to assess the risk of nephrotoxicity and other less common therapy-associated injuries (e.g., thrombotic microangiopathy, tubulointerstitial nephritis, glomerular diseases, and intratubular obstruction from medications) must also be considered [ 44 ].…”
Section: Managementmentioning
confidence: 99%